The process of didatic‑pedagogical training in health: learning perceived in the voice of postgraduate students - Abensur, Patricia Lima Dubeux; Carvalho, Gabrielle Passarini Mendes de; Ruiz‑Moreno, Lídia (ABCS Health Sciences, 2015)
Introduction: This study is part of the project “Teacher training: problem‑dialogical strategy with virtual environment use of learning” developed in the discipline Didatic‑Pedagogical Training in Health (DPTH), offered by the Higher Education Development Center on Health (CEDESS) in the Federal University of São Paulo (UNIFESP), in bimodal format (presence and distance). Objective: To analyze the learning built by graduate students in the teacher education process throughout DPTH discipline. Methods: The subjects of the research were eleven professionals from different areas of health. For the data collect, was requested to every postgraduate student, before the start of the course, an introduction letter, expressing their expectations and, in the end of the discipline, a self‑assessment of the learning built during the process. The thematic analysis came from the following guiding cores: initial expectations, learning built and future perspectives. Results: The expectations had manifested the intention to know techniques and tools to transmit the contents with centrality in the teacher, but even in minor proportion, was also expressed a desire to share information and reflect the education and health scenario in the country. In the core learning built, the students appreciated the strategies used in the discipline, emphasizing the construction and presentation of an education planning in small multiprofessional groups. In the future perspectives, many had shown the recognition to continue their teacher training to a better practice of the profession. Conclusion: the continuing education of the teacher training process appears to be a growing demand, which values this activity and its professionalisation.